Скельно-печерні природно-антропогенні комплекси в ландшафті Дністровськогоканйьону - Рідуш, Богдан (Рута, 2007)
Rocky landscapes of urochishche rank are widely spread on the eastern macroscope of Ukrainian Carpathians. They are connected to sandstone formations of flysch thickness of Palaeogene and Cretaceous. Few rock landscapes were artificially changed during the historic period while building defence constructions, sacral objects, dwellings etc. In some rocks artificial caves, grottoes and niches were cut out, the others were changed minimally just by rock-art engraving. The artificially changed complexes (landscapes) make up the separate category of natural-anthropogenic landscapes of low rank.